Exploiting thioether reactivity to label mycobacterial glycans - Stephanie R. Smelyansky; Chi-Wang Ma; Victoria M. Marando; Gregory H. Babunovic; So Young Lee; Bryan D. Bryson; Laura L. Kiessling (Proceedings of the National Academy of Sciences, 2025)
Mycobacterium tuberculosis ( Mtb ) is a leading cause of death worldwide. Mtb cell envelope glycans are potent virulence factors that play key roles in mediating infection of host tissues and modulating the host immune response. However, there are few ways to site-selectively modify and label these or any glycans to study their functions in disease. This gap arises because glycans generally lack functional groups amenable to bioconjugation strategies. Methylthioxylofuranose (MTX), a rare monosaccharide in select pathogenic mycobacteria, is an exception. MTX is appended to mannose-capped lipoarabinomannan (ManLAM), an antigenic glycolipid in the Mtb cell envelope implicated in downregulating the host immune system during infection. MTX is unique not only in its prevalence but also in its functionality—it contains a thioether not present in other glycans. We envisioned exploiting the MTX thioether to selectively label ManLAM with an oxaziridine probe. Here, we show that MTX-containing glycans can be labeled selectively in the test tube and live cells, highlighting the reactivity and accessibility of this motif. Our approach labels ManLAM efficiently despite the presence of protein methionine residues and can distinguish between different mycobacterial species. Using an oxaziridine equipped with a reporter, we could visualize ManLAM localization in live cells and a macrophage infection model, highlighting the stability of the label and the cell envelope in this environment. These studies will enable investigations of dynamic changes in a critical Mtb cell envelope component during infection. Moreover, the selective reactivity of thioethers can be leveraged to expand the repertoire of glycan bioconjugation strategies.